Theoretical emissions of landfill biogas and its energy use in Brazil: a bibliometric study - Zavarise, Julio Pansiere; Sagrillo Pimassoni, Yasmim; Pinotti, Laura Marina; Lopes Lemos, Ediu Carlos (Latin American Journal of Energy Research, 2021)
The incorrect disposal of solid urban waste (MSW) causes the emission of greenhouse gases (GHG), such as methane (CH4). Landfills are the main destination of MSW in Brazil and generate landfill biogas, which can be used for energy purposes. For landfills to be able to design biogas energy recovery and use systems, it is necessary to estimate the volume of gas that will be emitted during the landfill's useful life. For this, it is possible to make use of mathematical models, such as LandGEM and the model developed by the Intergovernmental Panel on Climate Change (IPCC). Considering the growth of publications about the energy valorization of landfill biogas, this study aimed to identify the trends and research gaps on the studies of theoretical CH4 emissions in Brazilian landfills and their subsequent energy use, through a bibliometric analysis. A growing trend was observed in the number of publications in the period from 2013 to 2020. India, China, and the United States are the countries that most published articles on the subject in the period of analysis. As for the models applied, there was a strong preference for the LandGEM model and for projects to convert biogas into electrical energy. Also noteworthy is the growth of generation distributed of electricity by landfill biogas. As research opportunities, there is the possibility of using the IPCC model to generate theoretical estimates of GHG emissions in Brazilian MSW landfills and the use of biomethane to generate heat and replace local demand for natural gas.
Keywords: methane; distributed generation; eletricity; solid waste; urban waste